Economic growth, comparative advantage, and gender differences in schooling outcomes: Evidence from the birthweight differences of Chinese twins - Mark R. Rosenzweig; Junsen Zhang (Yale University, Economic Growth Center, 2012)
Data from two surveys of twins in China are used to contribute to an improved understanding of the role of economic development in affecting gender differences in the trends in, levels of, and returns to schooling observed in China and in many developing countries in recent decades. In particular, we explore the hypothesis that these phenomena reflect differences in comparative advantage with respect to skill and brawn between men and women in the context of changes in incomes, returns to skill, and/or nutritional improvements that are the result of economic development and growth.
Keywords: J24; J16; I15; I25; O15; 330; schooling; gender; twins; China